2015
DOI: 10.15252/emmm.201404916
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin/IGF‐1 receptor signaling protects from mitochondria‐mediated kidney failure

Abstract: Mitochondrial dysfunction and alterations in energy metabolism have been implicated in a variety of human diseases. Mitochondrial fusion is essential for maintenance of mitochondrial function and requires the prohibitin ring complex subunit prohibitin-2 (PHB2) at the mitochondrial inner membrane. Here, we provide a link between PHB2 deficiency and hyperactive insulin/IGF-1 signaling. Deletion of PHB2 in podocytes of mice, terminally differentiated cells at the kidney filtration barrier, caused progressive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 42 publications
4
86
0
Order By: Relevance
“…Moreover, a loss of podocyte insulin sensitivity in the intact perfused glomerulus results in an albuminuric phenotype with features reminiscent of DN but in a normoglycaemic environment [12,15]. Recently, it has been shown that insulin signaling is also important in modulating other cellular processes in the podocyte including endoplasmic reticulum stress [14] and mitochondrial function [16]. Therefore, understanding the key signaling pathways and proteins that control insulin actions in this cell type is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a loss of podocyte insulin sensitivity in the intact perfused glomerulus results in an albuminuric phenotype with features reminiscent of DN but in a normoglycaemic environment [12,15]. Recently, it has been shown that insulin signaling is also important in modulating other cellular processes in the podocyte including endoplasmic reticulum stress [14] and mitochondrial function [16]. Therefore, understanding the key signaling pathways and proteins that control insulin actions in this cell type is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in body weight in the female PHB2 -/+ mice might be due to the relative loss of the repressive function of PHB2 on the role of estrogen in adipose tissue, as estrogen is known to have a role in adipose tissue homeostasis [77]. Moreover, a number of tissue-specific knockout mice models of PHB2 have been reported, which include pancreatic b cells, forebrain neurons, and kidney podocytes [6,16,17]. b Cell-specific knockdown of PHB2 results in impaired b cell function and diabetes [16], whereas its deletion in forebrain neurons leads to extensive neurodegeneration [6].…”
Section: Lessons From Phb Knockout Micementioning
confidence: 99%
“…b Cell-specific knockdown of PHB2 results in impaired b cell function and diabetes [16], whereas its deletion in forebrain neurons leads to extensive neurodegeneration [6]. The disease phenotypes of tissue-specific PHB2 knockout mice models have been attributed to the mitochondrial function of prohibitins [6,16,17]. However, a potential contribution of extra-mitochondrial membrane signaling functions of prohibitins may not be ruled out.…”
Section: Lessons From Phb Knockout Micementioning
confidence: 99%
See 2 more Smart Citations